The composition and differentiation potential of the duodenal intraepithelial innate lymphocyte compartment is altered in coeliac disease. Issue 8 (12th May 2015) - Schmitz, Frederike; Kooy-Winkelaar, Yvonne; Wiekmeijer, Anna-Sophia; Brugman, Martijn H; Mearin, M Luisa; Mulder, Chris; Chuva de Sousa Lopes, Susana; Mummery, Christine L; Staal, Frank JT; van Bergen, Jeroen; Koning, Frits
Abstract : Objective: Coeliac disease (CD), a gluten-induced enteropathy, alters the composition and function of duodenal intraepithelial T cells. The intestine also harbours four types of CD3-negative intraepithelial lymphocytes (IELs) with largely unknown function: CD56 − CD127 −, CD56 − CD127 +, CD56 + CD127 − and CD56 + CD127 + . Here we aimed to gain insight into the potential function of these innate IELs in health and disease. Design: We determined the phenotypes, relative abundance and differentiation potential of these innate IEL subsets in duodenal biopsies from controls and patients with CD or patients with refractory CD type II (RCDII). Results: Hierarchical clustering analysis of the expression of 15 natural killer and T cell surface markers showed that innate IELs differed markedly from innate peripheral blood lymphocytes and divided innate IEL subsets into two main branches: a CD127 − branch expressing high levels of interleukin (IL) 2/15Rβ but no IL-21R, and a CD127 + branch with the opposite phenotype. While CD was characterised by the contraction of all four innate IEL subsets, a selective expansion of CD56 − CD127 − and CD56 − CD127 + innate IEL was detected in RCDII. In vitro, in the presence of IL-15, CD56 − CD127 − IEL from controls and patients with CD, but not from patients with RCDII, differentiated into functional natural killer and T cells, the latter largely dependent on notch-signalling. Furthermore, compared with non-coeliac controls, CD56 − CD127 − IEL from patients with CD expressed more intracellular CD3ε and CD3γ and gave more pronounced T cell differentiation. Conclusions: Thus, we demonstrate previously unappreciated diversity and plasticity of the innate IEL compartment and its loss of differentiation potential in patients with RCDII.